The Transcription factor VvMYB5b contributes to the regulation of Anthocyanin and Proanthocyanidin biosynthesis in developing grape berries - Deluc, Laurent; Bogs, Jochen; Walker, Amanda R. (Plant physiology, 2008)
Among the dramatic changes occurring during grape berry (Vitis vinifera) development, those affecting the flavonoid pathway have provoked a number of investigations in the last 10 years. In addition to producing several compounds involved in the protection of the berry and the dissemination of the seeds, final products of this pathway also play a critical role in berry and wine quality. In this article, we describe the cloning and functional characterization of VvMYB5b, a cDNA isolated from a grape berry (V. vinifera ‘Cabernet Sauvignon’) library. VvMYB5b encodes a protein belonging to the R2R3-MYB family of transcription factors and displays significant similarity with VvMYB5a, another MYB factor recently shown to regulate flavonoid synthesis in grapevine. The ability of VvMYB5a and VvMYB5b to activate the grapevine promoters of several structural genes of the flavonoid pathway was confirmed by transient expression of the corresponding cDNAs in grape cells. Overexpression of VvMYB5b in tobacco (Nicotiana tabacum) leads to an up-regulation of genes encoding enzymes of the flavonoid pathway and results in the accumulation of anthocyanin- and proanthocyanidin-derived compounds. The ability of VvMYB5b to regulate particularly the anthocyanin and the proanthocyanidin pathways is discussed in relation to other recently characterized MYB transcription factors in grapevine. Taken together, data presented in this article give insight into the transcriptional mechanisms associated with the regulation of the flavonoid pathway throughout grape berry development.